Снегоход и олень в освоении таежного пространства - Vorob’ev, D. V.; Воробьев, Д. В. (Издательство Тюменского государственного университета, 2016)
The article discusses how the snowmobile allows the groups of taiga hunters who gave up reindeer herding to master vast geographical distances. It would seem that mechanical transport poorly compares poorly with reindeer because it requires continuous refuel which is impossible to produce in taiga. The source from outside is necessary. Nevertheless, the author shows that reindeer hunters from the settlement of Chirinda cover longer distances on snowmobiles during the hunting expeditions, than reindeer herders from the settlement of Sovrechka cover during of their annual migration. Chirinda people’s spatial strategy consists of hunting on remote territories with a large supply of gasoline and spare parts for the snowmobile with them. It permits them to refuel in other settlements on their way back while they are far from home. It is possible only on condition of the regular sales of the hunting products, which allows hunters getting necessary components in abundance. Рассмотрена стратегия освоения таежного пространства чириндинскими диковщиками.